2009
DOI: 10.1002/jnr.22315
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the expression and function of BRINP family genes during neuronal differentiation in mouse embryonic stem cell‐derived neural stem cells

Abstract: We previously identified a novel family of genes, BRINP1, 2, and 3, that are predominantly and widely expressed in both the central nervous system (CNS) and peripheral nervous system (PNS). In the present study, we analyzed the expression pattern of three BRINP genes during differentiation of mouse embryonic stem (ES) cell-derived neural stem cells (NSCs) and their effects on the cell-cycle regulation of NSCs. While there was no significant expression of any BRINP-mRNA expressed in mouse ES cells, BRINP 1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 65 publications
(103 reference statements)
0
17
0
Order By: Relevance
“…Of these, 11 were differentially expressed between MRT subgroups 1 and 2 (FDR < 0.05). 10 of the 11 genes were over-expressed in subgroup 1 (Table S4), including genes linked to neuronal differentiation (e.g., BEX1 , FAM5C/BRINP3; Coyle et al, 2011; Terashima et al, 2010; Vilar et al, 2006) or neural crest differentiation (e.g., ENC1; Rabadán et al, 2013). Conversely, of the 92 genes reported (Grupenmacher et al, 2013) as over-expressed in RTK relative to AT/RT, 21 were differentially expressed between sub-group 1 and 2, and all were over-expressed in sub-group 2 (one-sided Fisher’s exact p value = 1.193e-13; Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 11 were differentially expressed between MRT subgroups 1 and 2 (FDR < 0.05). 10 of the 11 genes were over-expressed in subgroup 1 (Table S4), including genes linked to neuronal differentiation (e.g., BEX1 , FAM5C/BRINP3; Coyle et al, 2011; Terashima et al, 2010; Vilar et al, 2006) or neural crest differentiation (e.g., ENC1; Rabadán et al, 2013). Conversely, of the 92 genes reported (Grupenmacher et al, 2013) as over-expressed in RTK relative to AT/RT, 21 were differentially expressed between sub-group 1 and 2, and all were over-expressed in sub-group 2 (one-sided Fisher’s exact p value = 1.193e-13; Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…A2 A receptor stimulation inhibits primary neurosphere formation and the proliferation of human and rodent neural precursor cells (Scemes et al ., 2003; Stafford et al ., 2007) suggesting that it may play a regulatory role in neuronal differentiation, which is one of the actions of BDNF during developmental period and is well presented in the increase of neurogenesis by oroxylin A (Terashima et al ., 2010; Jeon et al ., 2011; Noble et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…BRINP1 was initially identified as a tumour suppressor protein in human bladder cancer, as part of an effort to locate tumour suppressor genes in bladder cancer cells, and was given the name DBCCR1 (deleted in bladder cancer chromosome region 1) [60,61]. Subsequently, it was observed that ectopically expressing BRINP1 caused cell cycle arrest in cultured cell lines such as bladder cancer cells and the NIH 3T3 cell line [62,63], or even mouse embryonic stem cell-derived neural stem cells [58]. Independently, Kawano et al identified that BRINP1 was predominantly expressed in the central nervous system from early developmental stage to adulthood, and that the expression levels of these proteins were greatly enhanced upon stimulation with bone morphogenetic protein or retinoic acid, from which study the name of the proteins was proposed.…”
Section: Development-related Membrane Attack Complex/perforin Proteinsmentioning
confidence: 99%